Cytotoxic Granule Exocytosis From Human Cytotoxic T Lymphocytes Is Mediated by VAMP7 - Chitirala, Praneeth; Ravichandran, Keerthana; Galgano, Donatella; Sleiman, Marwa; Krause, Elmar; Bryceson, Yenan T.; Rettig, Jens (Frontiers in Immunology, 2019)
Cytotoxic T lymphocytes kill infected or malignant cells through the directed release of cytotoxic substances at the site of target cell contact, the immunological synapse. While genetic association studies of genes predisposing to early-onset life-threatening hemophagocytic lymphohistiocytosis has identified components of the plasma membrane fusion machinery, the identity of the vesicular components remain enigmatic. Here we identify VAMP7 as an essential component of the vesicular fusion machinery of primary, human T cells. VAMP7 co-localizes with granule markers throughout all stages of T cell maturation and simultaneously fuses with granule markers at the IS. Knock-down of VAMP7 expression significantly decreased the killing efficiency of T cells, without diminishing early T cell receptor signaling. VAMP7 exerts its function in a SNARE complex with Syntaxin11 and SNAP-23 on the plasma membrane. The identification of the minimal fusion machinery in T cells provides a starting point for the development of potential drugs in immunotherapy.